Improving the Treatment and Assessment of Moderate and Severe Pain in a Pediatric Emergency Department. (8th September 2016) - Chafe, Roger; Harnum, Debbie; Porter, Robert
Abstract : Background. The Janeway Children's Hospital previously enacted a number of measures to improve pain management for patients in its emergency department (ED). While improvements were demonstrated, rates for the timely assessment and treatment of pain remain below standards of care. Objectives. The study objectives are to investigate the impact of the previous attempts to improve the treatment of pain and to explore ways to further improve pain management in the ED. Methods. Key informant interviews and a focus group were conducted with nurses, physicians, and parents whose children were identified as having severe pain. Results. Interviews were conducted with 31 parents or children, 9 physicians, and 8 nurses. The focus group was attended by 15 nurses. Previous initiatives were viewed as improvements. Continued barriers include difficulties in accurately capturing the level of pain, issues in treating pain for specific types of patients, and inadequacy in addressing patients in severe pain. Conclusion. Changes in pain treatment protocols can result in positive impacts but are likely insufficient on their own to achieve desired standards of care. Consistent measurement and engagement with staff can identify additional opportunities for improving pain management within an ED setting.